Aerobic Exercise Training Attenuates Tumor Growth and Reduces Insulin Secretion in Walker 256 Tumor-Bearing Rats - Moreira, Veridiana Mota; da Silva Franco, Claudinéia Conationi; Prates, Kelly Valério; Gomes, Rodrigo Mello; de Moraes, Ana Maria Praxedes; Ribeiro, Tatiane Aparecida; Martins, Isabela Peixoto; Previate, Carina; Pavanello, Audrei; Matiusso, Camila Cristina Ianoni; Almeida, Douglas Lopes; Francisco, Flávio Andrade; et al. (Frontiers in Physiology, 2018)
Aerobic exercise training can improve insulin sensitivity in many tissues; however, the relationship among exercise, insulin and cancer cell growth is unclear. We tested the hypothesis that aerobic exercise training begun during adolescence can attenuate Walker 256 tumor growth in adult rats and alter insulin secretion. Thirty-day-old male Wistar rats engaged in treadmill running for 8 weeks, 3 days/week, 44 min/day, at 55% to 65% VO2max until they were 90 days old (TC= trained control). An equivalently aged group was kept inactive during the same period (SC= sedentary control). Then, half the animals of the SC and TC groups were reserved as the control condition and the other half were inoculated with Walker 256 cancer cells, yielding two additional groups (sedentary Walker and trained Walker). No death was observed in tumor-bearing rats. Body weight, food intake, plasma glucose, insulin levels and peripheral insulin sensitivity were analyzed before and after tumor cell inoculation. We also evaluated tumor growth, metastasis and cachexia. Isolated pancreatic islets secretory activity was analyzed. In addition, we evaluate mechanic sensibility. Our results showed improved physical performance according to the final workload and VO2max and reduced body weight in trained rats at the end of the running protocol. Chronic adaptation to the aerobic exercise training decreased tumor weight, cachexia and metastasis and were associated with low glucose and insulin levels and high insulin sensitivity before and after tumor cell inoculation. Aerobic exercise started at young age also reduced pancreatic islet insulin content and insulin secretion in response to a glucose stimulus, without impairing islet morphology in trained rats. Walker 256 tumor-bearing sedentary rats also presented reduced pancreatic islet insulin content, without changing insulin secretion through isolated pancreatic islets. The mechanical sensitivity test indicated that aerobic exercise training did not cause injury or trigger inflammatory processes prior to tumor cell inoculation. Taken together, the current study suggest that aerobic exercise training applied during adolescence may mitigate tumor growth and related disorders in Walker 256 tumor-bearing adult rats. Improved insulin sensibility, lower glucose and insulin levels and/or reduced insulin secretion stimulated by glucose may be implicated in this tumor attenuation.